In the future might we say that the Health Reform actually worked in Peru? - Castillo-Tarrillo, Giancarlo F. (2015)
Health reforms aim to universalize resources and services, seeking equity for a better quality of life in the population without any hindrance. We attended a symposium on health reforms in Latin America, organized in the context of the V Congress of the UNESCO Bioethics Network, which was unveiled different visions of health care reform applied in different countries such as Colombia, Brazil, Ecuador and Republic Dominican. Unfortunately, the reform implemented in the twentieth century in these countries has been a failure; so we asked a question, will it work in Peru ?, knowing that when we are doctors serve according to the Reformation, if it were to realize this.